2018
DOI: 10.1111/psyp.13296
|View full text |Cite
|
Sign up to set email alerts
|

The independency of the Bereitschaftspotential from previous stimulus‐locked P3 in visuomotor response tasks

Abstract: The Bereitschaftspotential (BP) and the P3 are well‐known ERPs usually observed during self‐paced and externally triggered tasks. Recently, the BP was also detected in externally triggered tasks before stimulus onset. However, doubts have been raised about the authenticity of the BP in these tasks due to possible overlaps with the previous trial P3 (hereinafter s‐1 P3). Here, we aim to test the authenticity of the BP in externally triggered tasks by comparing ERPs obtained during two visuomotor response tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 62 publications
(100 reference statements)
2
5
0
Order By: Relevance
“…For both tasks, the use of a jittered inter‐stimulus interval smoothed the temporal overlap between brain activities related to the preceding and to the current trial. In a previous manuscript of the present research group (Quinzi, Berchicci, Bianco, Perri, & Di Russo, 2019), we showed a lack of influence of post‐stimulus ERPs of the preceding trial on the current trial. A sketch of the two tasks is shown in Figure 1.…”
Section: Experiments 1: Visual and Auditory Drt Methodssupporting
confidence: 53%
“…For both tasks, the use of a jittered inter‐stimulus interval smoothed the temporal overlap between brain activities related to the preceding and to the current trial. In a previous manuscript of the present research group (Quinzi, Berchicci, Bianco, Perri, & Di Russo, 2019), we showed a lack of influence of post‐stimulus ERPs of the preceding trial on the current trial. A sketch of the two tasks is shown in Figure 1.…”
Section: Experiments 1: Visual and Auditory Drt Methodssupporting
confidence: 53%
“…The pre‐stimulus stage of processing allowed us to tell expectancy‐related activity from the one yielded by the stimulus administration. Since it was previously shown that with such a signal segmentation the late stimulus‐evoked ERPs do not contaminate the analysis of the preparatory activity in the next trial (Quinzi, Berchicci, Bianco, Perri, & Di Russo, 2019), we may assume that our findings are not driven by post stimulus processing for which hypnosis effects emerged until the P250 component (Perri et al., 2019). In other terms, unlike brain imaging techniques, ERPs allowed a sharp separation of the neural correlates of the disposition in receiving the stimulus from the activities of stimulus processing.…”
Section: Discussionmentioning
confidence: 74%
“…To evaluate pre-stimulus activity, EEG was segmented into 1300 ms epochs, starting 1100 ms before and ending 200 ms after stimulus onset. In line with previous studies [ 40 , 41 ], the baseline was applied to the first 200 ms (−1100/−900 ms) in which the signal was flat and stable. Given that the knowledge of stimulus category was unpredictable at this stage of processing, target and non-target trials were averaged together.…”
Section: Methodsmentioning
confidence: 99%